From here to there : inventions that changed the way the world moves - Kirkfield, Vivian (Houghton Mifflin Harcourt, 2021)
"Celebrating the invention of vehicles, this collective biography tells the inspiring stories of the visionaries who changed the way we move through air, water, and land. Perfect for fans of Mistakes that Worked and Girls Think of Everything"--